A Study of Domesticated/Foreignized English Translation of Idiomatic Phrasal Verbs/Idioms from Urdu Novel “Bastī” - Batool, Itrat; Naz, Dr. Aqlima (Al-Qanṭara, 2025)
This paper explores translation of Idiomatic Phrasal Verbs/Idioms from Urdu to English, applying Venuti’sstrategies for translating idioms. The study examinesthe translation under Venuti’s strategies for translation known as Domestication and Foreignization. Venuti’s ideas of translation are considered here because of his vide range of strategies including translation of cultural specific items (CSIs) that must be kept in the view while translating Idiomatic Phrasal Verbs/Idioms. The textual samples are taken from Urdu Novel “Bastī” by Intizār Husain and its English translation by Francis Pritchett. The study shows how different strategies may be taken for translating Idiomatic Phrasal Verbs/Idioms referring to the context and where the selection of strategy is appropriate or inappropriate. The results are compiled quantitatively with a qualitative discussion about the strategy taken for the translation.